Combustion synthesis assisted water atomization-solid solution precipitation: A new guidance for nano-ZTA ceramics. Issue 14 (November 2019) - Yu, Wanjun; Zheng, Yongting; Yu, Yongdong; Su, Xiaoyue
Abstract: It is difficult to synthesize ceramics with ultra-fine nanostructures because of inevitable grain growth during the sintering process. In this work, a novel technique, i.e. combustion synthesis assisted water atomization (CSAWA) method, was invented to synthesize supersaturated Al2 O3 /ZrO2 solid solution powders. The huge cooling rate supplied by CSAWA greatly improved the solubility of Al 3+ in ZrO2 lattice. Subsequently, the synthesized powders underwent a solid solution precipitation process. The ultra-fine ZrO2 nanoparticles and Al2 O3 matrix are precipitated from metastable phase, and the ZrO2 nanoparticles are uniformly dispersed in Al2 O3 matrix. Simultaneously, the powders were densified and formed compact ZTA ceramics. Together with detailed microstructure, phase composition, interface characteristic, mechanical properties, as well as the toughening mechanisms were collaboratively outlined. CSAWA-SSPP not only produces impressive comprehensive properties, but also much lower costs and simpler process than currently methods, which opens up a new route to industrially produce nano-ZTA ceramics with high performance.